Biological Aspects Reproduction of Betok Fish (Anabas testudineus Bloch) in the Peat Swamp Area in the Pelalawan Village, Pelalawan District, Riau Province - Putri, Dea Ananda; Putra, Ridwan Manda; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Anabas testudineus is one of freshwater fish living in the peat swamp area in the Pelalawan Village. A study aims to determine the reproductive biological aspect of betok fish. The fish was sampled 6 times, from March to May 2019. Parameters measured were sexuality, sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Result shown that there was 102 fishes, 60 males and 42 females. Sex ratio of males and females was 1,4:1. In each sampling time there were male and females fishes in I, II, III and IV gonad maturity level. The gonad somatic index (GSI) in males were around 0,60-0,96% and females were around 0,62-2,79%. The female’s fecundity were around 2.395-4.862 eggs/fish, and egg diameter ranged from 0,5-0,8 mm.Keywords : Anabas testudineus, Sex ratio, fecundity, Gonad Maturity Level, Gonad Somatic Index.